Praxeological Analysis of Mathematics Textbooks for Class XI High School Students on Arithmetic and Geometric Sequences - Qania Agustika Siagian; Aswin Aswin; Tatang Herman (EduMa: Mathematics education learning and teaching, 2023)
This study aims to analyze one of the mathematics textbooks published by the Ministry of Education and Culture. Then, the researcher will provide recommendations regarding the presentation of easy-to-understand material based on analysis of techniques, technology, and theory on each problem given by students' mathematics textbooks. This type of research is qualitative with a didactic anthropological theory approach, especially in praxeology. Data collection techniques in the library by reading, recording and processing these sources as research material. Researchers choose books based on the criteria needed to obtain relevant data. These criteria include (1) there is a problem in presenting mathematical material, (2) there is an author's name, and (3) publications from the Ministry of Education and Culture. The researcher found problems in the 2017 revised edition of class XI students' mathematics textbooks finding formulas and examples of arithmetic and geometric sequences. The study results showed several problems presenting the material for arithmetic and geometric sequences, which would raise student learning barriers. The identified Learning barriers are ontogenic, epistemological, and didactical obstacles. With these obstacles, the researcher provides alternative designs which are expected to minimize the occurrence of student learning barriers. So that the design alternatives provided can reduce obstacles for students in thinking and understanding the material of arithmetic and geometric sequences